EXPERIENCE OF USING AUTPLASMA CONTAINING PLATELETS IN THE TREATMENT OF SYNECHIA OF THE UTERINE CAVITY - Ольга Юрьевна Цыганкова; Кирилл Петрович Кропмаер; Елена Николаевна Кравченко (The Publishing House Medicine and Enlightenment, 2020)
The problem of intrauterine synechia (IUS) is still a major medical and social problem. The prognosis for reproductive function and the quality of later life during gynecological operations is largely determined by the possible adhesive process. The trigger for the formation of IUS is trauma to the basal layer of the endometrium, which can be caused by various factors, including intrauterine interventions. Currently, the «gold standard» for the diagnosis and treatment of IUS is hysteroscopy and their separation. To prevent the formation of adhesions, hormone replacement therapy is traditionally used to accelerate the proliferation of the normal endometrium, special intrauterine devices or the introduction of balloon catheters, anti-adhesion barriers. However, there remains a high risk of relapse, and when pregnancy occurs, the development of its complications. The use of autoplasma containing platelets in the treatment of synechia of the uterine cavity helps reduce the risk of relapse of the IUD after separation, restoration of menstrual and reproductive functions.